2019
DOI: 10.1097/ajp.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tonic Spinal Cord Stimulation on External Mechanical and Thermal Stimuli Perception Using Quantitative Sensory Testing

Abstract: Objectives: Tonic spinal cord stimulation (SCS) is currently used to treat neuropathic pain. With this type of stimulation, an implantable pulse generator generates electrical paresthesias in the affected area through 1 or more epidural leads. The goal of this study was to evaluate the impact of tonic SCS on the sensory perception of chronic pain patients using quantitative sensory testing (QST). Materials and Methods: Forty-eight patients (mean age: 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Qualitative fieldnotes were collected among 48 patients with chronic neuropathic pain during an independent multicenter QST study. 21 Recruitment for the QST study occurred between January 2016 and November 2017 at three research centers: CHU de Québec – Université Laval, Canada; University of Toledo Medical Center, USA; and Centre hospitalier de l’Université de Montréal, Canada. Inclusion criteria were the following: older than 18 years old; French or English speaker; diagnosed with complex regional pain syndrome and failed back surgery syndrome (meeting the International Association for the Study of Pain’s criteria 22 , 23 ); implanted with a spinal cord stimulator device for at least 6 months; having the same programming parameters or medication for at least 30 days before testing; using tonic stimulation mode only; feeling the paresthesia induced by tonic spinal cord stimulation (SCS) in one or both legs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative fieldnotes were collected among 48 patients with chronic neuropathic pain during an independent multicenter QST study. 21 Recruitment for the QST study occurred between January 2016 and November 2017 at three research centers: CHU de Québec – Université Laval, Canada; University of Toledo Medical Center, USA; and Centre hospitalier de l’Université de Montréal, Canada. Inclusion criteria were the following: older than 18 years old; French or English speaker; diagnosed with complex regional pain syndrome and failed back surgery syndrome (meeting the International Association for the Study of Pain’s criteria 22 , 23 ); implanted with a spinal cord stimulator device for at least 6 months; having the same programming parameters or medication for at least 30 days before testing; using tonic stimulation mode only; feeling the paresthesia induced by tonic spinal cord stimulation (SCS) in one or both legs.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, our first objective was to organize and classify qualitative fieldnotes of sensory abnormalities collected during a previous QST study. 21 A second objective was to generate a qualitative interview guide, based on these qualitative results, that could be included in the traditional QST procedure as a step towards the development of a mixed methods approach.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review investigated QST changes with SCS and concluded that conventional tonic SCS does not seem to have an influence on most QST parameters 45 . The inconsistent QST results that Bordeleau et al found were suggested to potentially be related to a broad range of pain disorders included, heterogeneity in the QST methods used, and heterogeneity in the study designs.…”
Section: Discussionmentioning
confidence: 99%
“…Early SCS studies by Lindblom and Meyerson, and Eisenberg et al have reported significant effects of stimulation on VDT in chronic pain patients (69, 70). However, more recent studies have reported minor effects or no effects on VDT with SCS (28, 51, 71). We anticipated that SCS and DRGS treatment would significantly modulate (increase) VDT via stimulation‐induced excitation of low‐threshold, large‐diameter Aβ fibers in the dorsal columns of the spinal cord, and in the dorsal root ganglia, at spinal levels innervating the pain region(s) or corresponding dermatome of the body, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because our sample size was small ( n = 16), and our dataset was not normally distributed, we used the Wilcoxon signed‐rank test, a non‐parametrical test for statistical comparisons, to assess for treatment effects of SCS and DRGS. Previously published SCS studies have used the Wilcoxon signed‐rank test for comparing paired samples of non‐normally distributed data in relatively small and large populations of chronic pain patients (29,51). We calculated the effect size (or “ r ” value) for the Wilcoxon's test using previously established formula for this test (52,53).…”
Section: Methodsmentioning
confidence: 99%